An Intriguing Approach to The Fractional Mellin Transform Method (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
We propose an adapted Mellin transform method that gives the solution of a fractional di ¤erential equation with variable coefficients in ordinary domain. After we mention a transformation of cosmic time to individual time (CTIT), we explain how it can reduce the problem from fractional form to ordinary form when it is used with Mellin transformation, via an example for 0 < alpha < 1; where alpha is the order of fractional derivative. Then, we give an application of the results.